People and organizational management in construction - Naoum, S. G. (ICE, 2011)
Using case studies and examples from the construction industry, this guide blends management concepts and theories with practice to explain the interactions between people at work, the management and the external environment, an understanding of which is essential for an organization's success.
Previous ed.: 2001.
Keywords: Construction industry -- Management.; Organizational behavior.; elektronické knihy; electronic books